he Spaces of Mary of Egypt’s Lust in Medieval Hispanic Verse and Prose (MSS. ESC. K-III-4 and h-I-13) - Zubillaga, Carina (Revista Melibea, 2024)
The western side of the story of Saint Maria Egipciaca is attested in two Hispanic versions of the legend of the repentant prostitute, found in Esc. MSS. K-III-4 and hI-13. The comparison of these versions, respectively in verse and prose, allows us to study the stylistic transformations undergone by the stages of the saint's life, from her youth to her old age, which unfold over time and take on specific spaces representative of both sin and penitence. If the desert is the space that refers the penitent stage, since the more than forty years she spends there are what define the sanctity she will attain, the spaces of lust as the sin of her youth are indicative of the mobility of sin in the period, both for its constitutive quality based on constant movement and for its voluble character, as opposed to the stability that its purgation will require, as will be studied in the present work.